Rozwiązane

b) 2(x2 – 4) = 2x² - 4x + 10
d) x3 – (2 - x) = 4(0,5x3
+ x)
Daje najjj



B 2x2 4 2x 4x 10 D X3 2 X 405x3 X Daje Najjj class=

Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

b)

2(x²-4) = 2x²-4x+10

2x²-8=2x²-4x+10

2x²-2x²+4x=10+8

4x=18

x=4,5

d)

x³ - (2-x³) = 4 (0,5x³+x)

x³-2+x³ = 2x³+4x

2x³-2=2x³+4x

2x³-2-2x³-4x=0

-4x=2

x = -1/2

Zadanie

b)

2(x² - 4) = 2x² - 4x + 10

2x² - 8 = 2x² - 4x + 10    l -2x²; +4x

4x - 8 = 10    l +8

4x = 18    l :4

x = 4,5

d)

x³ - (2 - x³) = 4(0,5x³ + x)

x³ - 2 + x³ = 2x³ + 4x    

2x³ - 2 = 4x + 2x³   l -2x³

-2 = 4x

4x = -2    l :4

x = -0,5